Value-matters - Espeland, Wendy Nelson (2001)
When we think about the value of something, we often focus on what we value or how much we value something. This paper argues that how we value is an important social and political relationship. Drawing on examples taken from art, federal water projects, and people's efforts to resist them, the author describes some of assumptions behind, and the consequences of, people's efforts to capture or convey value through processes of commensuration: the transforming of qualitative relations into a common metric. The effects of commensuration are complex and variable; as a strategy of valuing, commensuration can create new objects and new relationships between objects; it can systematically exclude certain kinds of valued goods, relations, or people. Commensuration as a means of integrating disparate values can also distort the nature of people's investments in politically potent ways. - Reproduced
Keywords: Value systems